Manajemen komunikasi pariwisata: bone bolango dan pandemi covid-19 - Taufik R. Talalu; Bondan Ariyanto Sadewo (Islamic Communication Journal, 2021)
The decrease of tourist visits in Bone Bolango Regency as a portrait of Covid-19 impact indicates the strategic objectives of Tourism and Creative Economy Department (Disparekraf), which is to increase the number of tourists, cannot be achieved. The purpose of this study is to identify the department’s method to increase the number of tourists in order to restore the tourism sector in the region, as well as the application of tourism communication management, specifically the settings of tourism communication channel by the department. The data was collected using interviews, observation, and documentation study to be analyzed based on the four stages in the interactive model by Miles Huberman; namely data collection, data reduction, data display, and conclusion. The findings showed the settings of the communication channel was expected to restore the tourism sector in Bone Bolango Regency with both internal and external audience, while WhatsApp and Zoom were used for internal audiences. Facebook, Instagram, and the website were used for external audiences. These channels were used because it was more practical and reached more external audiences. However, it did not contain attractive and complete informations regarding tourist attraction in Bone Bolango Regency.